Sailing between Scylla and Charybdis: Mayelane v Ngwenyama - Kruuse, Helen; Sloth-Neilsen, Julia (Potchefstroom Electronic Law Journal, 2017)
Mayelane v Ngwenyama 2013 4 SA 415 (CC) is arguably the most important judgment concerning the recognition of customary marriages in recent times. This article attempts to unpack some of the many issues that arise from the case, namely: (a) the practical difficulties associated with ascertaining living customary law and the problems of identifying legal versus social norms; (b) the meaning of consent as a requirement of a customary marriage; (c) the implications of the case for equality between multiple wives in a customary marriage, and as between wives across customary marriages of different cultural traditions; and (e) the implications of the case for equality considerations more broadly. While the authors sympathise with the court in respect of the complex decision before it, it questions the Court’s method and result, specifically for the equality rights of a second (or further) "wife" in a Vatsonga customary marriage. The authors suggest that the issues should be put to democratic deliberation by the legislative arm, rather than leaving courts in the unenviable position of having to decide these matters.